Synodality: Communion, participation and mission in action - Resane, Kelebogile T. (HTS teologiese studies, 2023)
The article used the current Synod on Synodality 2021–2023 as a road map to reinforce understanding of synodality, communion, participation and mission. It extracted some theological lessons the non-Catholics can learn from this synod. The essay is not here to defend or to critique Synod on Synodality 2021–2023, but to expand it and to conscientise the non-Catholic adherents of Christian faith of the importance of synodality as a theological dictum. The starting point was the historical and etymological background of synodality and moved into synodical understanding from the Reformed traditions. Three of these traditions in South Africa were highlighted to demonstrate how some Reformed Churches had been on a synodical journey. These three are the Dutch Reformed Church (NGK), Lutherans and the United Congregational Church. The three sub-themes of synodality, that is communion, participation and mission were examined and studied to deepen the ecumenical understanding of this Synodality. The literature, past and present, on the three sub-themes was the basis of the argument. There were some references to electronic sources as the Synod is still sitting and is expected to conclude in October 2023. The conclusion was an appeal to the universal church to journey together to meet [koinonia], listen to each other and to the Spirit [participate], and discern [mission] the direction the church is to take to reach the world with the love of Christ. The people of God are to engage in communion by re-appreciating the love of Christ that leads into and enhances communion. The Synod is a call for participation of all members of the body of Christ to respectfully listen to the Holy Spirit and each other in order to guide the church in the world.Contribution: The Protestants, especially of Reformed tradition always ignore important events such as Synod on Synodality 2021–2023. This Synod reminds Protestants of the importance of communion, participation and mission in the world.